Analysis of Wind Regime and Sand Transport Potential in the Marginal Ergs of the Namak Lake, Central Iran - Ariyan Allahveisi; Mehran Maghsoudi; Abolfazl Qojezadeh Helani; Mehdi Safari namivandi (مطالعات جغرافیایی مناطق خشک)
Aim: This study aims to analyze the wind regime and estimate sand drift potential in the ergs along the southern margin of Qom Salt Lake. It also investigates how erosive wind direction and strength influence the formation of aeolian geomorphological features, improving the understanding of morphodynamic processes in the region.Materials and Methods: To achieve the research objectives, 20 years of meteorological data from five synoptic stations around the study area were used. WRPLOT View 7 and Sand Rose software were employed to plot wind rose and sand rose diagrams and to analyze the DP, RDP, RDD, and UDI indices. A geomorphological map of the area was also prepared, and sand transport pathways were interpreted.Findings: At Qom and Aran & Bidgol stations, dominant winds blow from the north and northwest, producing the highest sand transport potential along the northeast–southwest axis. Kashan, Garmsar, and Ardestan stations experience winds primarily from the east and southeast, with Garmsar and Ardestan showing multidirectional patterns at obtuse angles, significantly influencing sediment displacement and dune dynamics.Conclusion: The findings indicate that the directional variability and intensity of winds in the study area directly affect sand displacement and accumulation. The prevailing pattern of sand movement corresponds to the orientation of the region’s sand dunes, which are primarily directed toward the east and southeast. It was also determined that much of the transported sediment originates from surrounding alluvial fans with diverse lithological compositions. These results confirm the crucial role of climatic factors, topography, and sediment sources in the dynamism of aeolian landforms and geomorphic processes in the region.Innovation: This study applies a vector-based, quantitative approach to sand drift analysis using wind indices, helping explain dune formation patterns and predict future morphological changes. These results support better resource management and planning in arid environments.